Onset of deep drainage and salt mobilization following forest clearing and cultivation in the Chaco plains (Argentina) - Amdam, M. Laura; Aragón, Myriam Roxana; Jobbagy Gampel, Esteban Gabriel; Volante, Jose Norberto; Paruelo, José María (Wiley, 2019)
Semiarid sedimentary plains occupied by dry forest ecosystems often display low groundwater recharge rates and accumulation of salts in the soil profile. The transformation of these natural systems to rain‐fed agriculture has led to raising water tables and a slow, but steady, process of groundwater and soil salinization in vast areas of Australia. In the semiarid plains of Chaco (central South America), unprecedented deforestation rates are taken place. Based on deep soil sampling (0–6 m) in seven paired stands under natural dry forest, rain‐fed agriculture and pasture, with different age of clearance (>30 years, 20 and 3 years) in Salta, Argentina, we provide evidence of groundwater recharge increase and onset of salt mobilization in areas where forests were replaced by annual croplands. Soils with higher water and lower chloride content are evidence of deep percolation and salt leaching. In Salta, stands subject to 30 years of rain‐fed cultivation had profiles with 30–46% higher moisture content and 94% lower chloride stocks compared to dry forest (0.05 ± 0.04 kg/m2 versus 0.77 ± 0.4 kg/m2). Estimates of groundwater recharge based on the displacement of chloride peaks suggested values of 27–87 mm yr−1 for agricultural soybean stands, and 10.4 mm yr−1 for pastures. While hydrological shifts in the regional groundwater system are poorly monitored and understood, our findings show that it is potentially sensitive to land use changes and to salinization processes.